Toxicological impact of acute exposure to E171 food additive and TiO2 nanoparticles on a co-culture of Caco-2 and HT29-MTX intestinal cells - Dorier, Marie (2019)
TiO2 particles are widely used in products for everyday consumption, such as cosmetics and food; their possible adverse effects on human health must therefore be investigated. The aim of this study was to document in vitro impact of the food additive E171, i.e. TiO2, and of TiO2 nanoparticles, on a co-culture of Caco-2 and HT29-MTX cells, which is an in vitro model for human intestine. Cells were exposed to TiO2 particles three days after seeding, i.e. while they were not fully differentiated. Cell viability, reactive oxygen species (ROS) levels and DNA integrity were assessed, by MTT assay, DCFH-DA assay, alkaline and Fpg-modified comet assay and 8-oxo-dGuo measurement by HPLC-MS/MS. The mRNA expression of genes involved in ROS regulation, DNA repair via base-excision repair, and endoplasmic reticulum stress was assessed by RT-qPCR. Exposure to TiO2 particles resulted in increased intracellular ROS levels, but did not impair cell viability and did not cause any oxidative damage to DNA. Only minor changes in mRNA expression were detected. Altogether, this shows that E171 food additive and TiO2 nanoparticles only produce minor effects to this in vitro intestinal cell model.